Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevb.86.045415
|View full text |Cite
|
Sign up to set email alerts
|

Advanced optical effective medium modeling for a single layer of polydisperse ellipsoidal nanoparticles embedded in a homogeneous dielectric medium: Surface plasmon resonances

Abstract: We calculate, in the quasistatic coupled dipole approximation, the analytical expressions of the effective dielectric tensor of a single layer of polydisperse ellipsoidal nanoparticles with two of their principal axes in the layer's plane and embedded in a homogeneous dielectric medium. The organization (isotropic or anisotropic) and orientation (without or with a preferential in-plane orientation) of the nanoparticles is taken into account, together with their (possibly correlated) in-plane size, in-plane pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…17,18 However, preparation routes unavoidably conduct to NPs showing a shape distribution which induces drastic changes in the optical properties of NP assembly. [19][20][21][22] Indeed, by combining Gibbs free energy calculation to discrete dipole approximation, Noguez et al [23][24][25] have shown that the morphology and so the optical properties of NPs depend on the temperature used to synthesize them. In addition, as reported by Sayah et al, 19 silver prolates grown in a mesoporous silica matrix exhibit a large length distribution which induces an inhomogeneous broadening of the L-SPR bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, preparation routes unavoidably conduct to NPs showing a shape distribution which induces drastic changes in the optical properties of NP assembly. [19][20][21][22] Indeed, by combining Gibbs free energy calculation to discrete dipole approximation, Noguez et al [23][24][25] have shown that the morphology and so the optical properties of NPs depend on the temperature used to synthesize them. In addition, as reported by Sayah et al, 19 silver prolates grown in a mesoporous silica matrix exhibit a large length distribution which induces an inhomogeneous broadening of the L-SPR bands.…”
Section: Introductionmentioning
confidence: 99%
“…Toudert et al 21 have introduced the NP shape distribution in the Yamaguchi model. 26 However, this model can only be applied for two dimensional arrays of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…in the form of nanoparticles, have unique physical and chemical properties compared to their bulk form [1]. Among them, silver (Ag) and gold (Au) are the two most studied plasmonic materials since when they are embedded in a dielectric matrix they manifest localized surface plasmon resonances (LSPR) in the visible range [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…The LSPR effect occurs when the metallic nanoparticles are well-separated and have dimensions significantly smaller than the wavelength of the incident electromagnetic field [3]. It is responsible for a broad and intense absorption of light in the vicinity of the resonance frequency and the enhancement of the local electromagnetic field [1]. The LSP resonance frequency, bandwidth and peak height depend markedly on the nanoparticles composition, their shape, size and size distribution and also on the host dielectric matrix [5].…”
Section: Introductionmentioning
confidence: 99%
“…Spectrum-averaged refractive indices insufficiently describe nanoantennas supported by emergent materials like transition metal dichalcogenides [13]. Maxwell-Garnett and effective medium [14][15][16][17] analytic approaches describe mode energy shifts for random [17][18][19] and ordered [20][21][22] nanospheres using Mie theory and the coupled dipole approximation (CDA), respectively, but are limited to real-valued dielectric substrates with near-zero dispersion.…”
Section: Introductionmentioning
confidence: 99%